2022
DOI: 10.3390/ijerph191912640
|View full text |Cite
|
Sign up to set email alerts
|

Association between E-Cigarette Advertising Exposure and Use of E-Cigarettes among a Cohort of U.S. Youth and Young Adults

Abstract: Youth and young adult (YYA) use of e-cigarettes increased rapidly between 2010 and 2019 in the United States, during which exposure to e-cigarette advertising was also increased. We aimed to examine whether exposure to e-cigarette advertising among YYAs may lead to subsequent e-cigarette use. A cohort of 3886 YYAs ages 13–24 was recruited from two survey panels in 2018 and followed up until 2019. Survey data were collected online and by telephone. The primary outcome was past 30-day use of e-cigarettes at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 50 publications
0
10
1
Order By: Relevance
“…Therefore, policies to counteract the impact of youth-oriented e-cigarette advertising can include regulating and restricting ecigarette advertising online and social media, as in findings in previous studies. 33,35 This study also pointed out that referral marketer invitation also motivated e-cigarettes use. Although this source was strictly banned in Vietnam, but the violation could still be easily seen in public places with many young people, suggesting policies and regulations that restrict this type of youth-oriented e-cigarette advertising may be warranted.…”
Section: Exposure To Sources Of E-cigarettes Advertisements Among Ado...mentioning
confidence: 63%
See 1 more Smart Citation
“…Therefore, policies to counteract the impact of youth-oriented e-cigarette advertising can include regulating and restricting ecigarette advertising online and social media, as in findings in previous studies. 33,35 This study also pointed out that referral marketer invitation also motivated e-cigarettes use. Although this source was strictly banned in Vietnam, but the violation could still be easily seen in public places with many young people, suggesting policies and regulations that restrict this type of youth-oriented e-cigarette advertising may be warranted.…”
Section: Exposure To Sources Of E-cigarettes Advertisements Among Ado...mentioning
confidence: 63%
“…Our suggestion is in lined with other studies. 35 Visual optimization such as color may influence and draw attention of readers on e-cigarette advertisements, 36 this study also showed that attractive color of e-cigarette advertisements increased the risk of smoking. This is consistent with findings from previous studies 14,16,34 when some media sources like TV, the Internet, magazines, etc.…”
Section: Exposure To Sources Of E-cigarettes Advertisements Among Ado...mentioning
confidence: 65%
“…ENDS are advertised as safer alternatives compared to traditional combustible tobacco products, although concerns over their use have continued to grow [ 38 , 39 ]. Recent evidence indicates hazardous chemical compounds are prominent in pod-type ENDS-emitted aerosol, which when characterized within the context of individual vaping frequency or patterns may lead to exposure variances with unknown consequences [ 7 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Morgenstern et al (2013) discovered that the more such ads youth view (for example, in their neighborhood or in publications), the more likely they are to start smoking, even if they were previously at low risk of smoking. Similarly, high school as well as middle school students who had external communication to cigarette advertising had a greater likelihood of using cigarettes (Do et al, 2022). Agha and Meekers (2010) investigated the impact of an advertising campaign based on condom use in urban Pakistan.…”
Section: Youths Attitude Towards Social Advertisementmentioning
confidence: 99%